Brief Report: M‐Ficolin Levels Reflect Disease Activity and Predict Remission in Early Rheumatoid Arthritis. Issue 12 (27th November 2013) - Ammitzbøll, Christian G.; Thiel, Steffen; Jensenius, Jens C.; Ellingsen, Torkell; Hørslev‐Petersen, Kim; Hetland, Merete L.; Junker, Peter; Krogh, Niels S.; Østergaard, Mikkel; Stengaard‐Pedersen, Kristian
Abstract : Objective: To assess plasma M‐ficolin concentrations in disease‐modifying antirheumatic drug (DMARD)–naive patients with early rheumatoid arthritis (RA), to investigate the correlation of M‐ficolin concentrations with disease activity markers, and to determine the predictive value of M‐ficolin with respect to the Disease Activity Score in 28 joints (DAS28). Methods: The study group included 180 DMARD‐naive patients with early RA who participated in a randomized controlled trial of methotrexate and intraarticular glucocorticoids plus either adalimumab or placebo/adalimumab. One hundred healthy control subjects and 51 patients with chronic RA were also assessed. A sandwich‐type time‐resolved fluorometric immunoassay was used for quantification of plasma M‐ficolin. Results: At baseline, M‐ficolin levels were highest in the group of DMARD‐naive patients with newly diagnosed active RA, and the level in these patients decreased 26% after 1 year of aggressive treatment. The baseline M‐ficolin level correlated with 5 of 7 disease activity markers, including the DAS28 and the Health Assessment Questionnaire (HAQ), and a similar pattern of correlations was observed at 1 year. Multiple logistic regression analysis showed that an elevated M‐ficolin level at baseline was the strongest predictor of not achieving either DAS28 remission (odds ratio [OR] 4.18, 95% confidence interval [95% CI] 2.02–8.63) or low disease activity (OR 2.45, 95% CI 1.13–5.28) at 1 year. The presence of a baseline M‐ficolin level in the lowest quartile resulted in sensitivity of 29%, specificity of 93%, and positive predictive value of 95% for low disease activity at 1 year. Conclusion: In patients with early RA, elevated plasma M‐ficolin levels correlated with a high DAS28 and a high HAQ score at baseline and 1 year. A low M‐ficolin level was the strongest predictor of remission and low disease activity in a multivariate analysis.